Evaluating Neutralizing Antibodies in Hantavirus-Infected Patients Using Authentic Virus and Recombinant Vesicular Stomatitis Virus Systems - Punya Shrivastava-Ranjan; Jamie A. Kelly; Laura K. McMullan; Deborah Cannon; Laura Morgan; Payel Chatterjee; Shilpi Jain; Joel M. Montgomery; Mike Flint; César G. Albariño; Christina F. Spiropoulou (Viruses)
Hantaviruses, including the Sin Nombre virus (SNV) and Andes virus (ANDV), are associated with severe global health risks, causing high mortality rates in hantavirus pulmonary syndrome (HPS) patients. Neutralizing antibodies are essential for virus clearance and survival, making neutralization assays critical for understanding immunity and evaluating therapeutic strategies. In this study, we developed a recombinant vesicular stomatitis virus (VSV)-based surrogate system expressing SNV and ANDV glycoproteins (GPCs), enabling neutralization studies under biosafety level 2 conditions. The neutralization titers obtained with the VSV-based system closely matched the findings from authentic hantavirus assays performed under biosafety level 3 conditions, confirming its potential as a useful tool for determining immune responses and advancing hantavirus research.